Conceptual design and simulation of a plant for the production of high purity (S)-ibuprofen acid using innovative enzymatic membrane technology - Lau, John; Gonawan, F.; Bhatia, S.; Kamaruddin, A.; Uzir, M. (Elsevier BV, 2011)
(S)-Ibuprofen is a low volume but high value pharmaceutical product which is categorized as non-steroidal anti-inflammatory drug (NSAID). This precious chiral drug may be produced using racemic ibuprofen as raw material through the dynamic kinetic resolution. In this work, a simulation of (S)-ibuprofen production is carried out using ASPEN PLUS ® process simulation software. A pilot scale production with the capacity of 500g/day of (S)-ibuprofen acid is considered in the present study. The product is synthesized through a three-step process: (i) substrate preparation via esterification; (ii) enzymatic dynamic kinetic resolution of substrate ester and (iii) product purification. Mass and energy balances of major equipment were calculated. The performance of the enzyme-mediated membrane reactor (EMR) was investigated by manipulating substrate and base concentrations as well as the flow rates. Besides, a number of issues related to the evaporation and crystallization of the product were identified and addressed. It was found that the optimum operating condition of EMR at 40°C, 50-100ml/min lumen flow rate with substrate and base concentrations, respectively at 10-20mM and 60-100mM, gave 0.92 conversion and 0.9 ee p of the product. An overall yield of 82.5% product crystal was achieved by operating the cooling-crystallizer in the temperature range of 5-10°C. © 2010 Elsevier B.V.